Application of Sponge City strategies in flood susceptible areas; Hatay, Antakya example - Aksoy, Onur; Erken, Kamil; Sokmen, Eren Dagra (Springer, 2025)
Recently, floods have affected many areas due to the deterioration of the precipitation regime and improper land use. To mitigate these impacts, it is essential to implement sustainable urban drainage systems, such as Sponge City strategies, particularly in vulnerable regions. The study aims to minimize the possible effects of flood disasters by developing Sponge City proposals in high flood susceptibility areas in the center of Hatay, where the loss of life and a major structural disaster occurred after the February 6, 2023, Kahramanmara & scedil; earthquake. Firstly the study flood susceptibility analysis was carried out at the Hatay center. The SWAT + module was used while performing the flood susceptibility analysis. The SWAT + module was employed to ascertain the locations of areas exhibiting high, moderate, and low flood susceptibility within the Hatay center. Analysis has showed that %89.24 of agricultural area and % 6.47 of built-up areas in the center of Hatay are under serious threat. The study is unique in that it proposes SC recommendations in flood susceptibility areas using geographic information systems. The impact of flood-related damages can be mitigated through the implementation of Sponge City applications in areas with high flood risk. Many such applications have been proposed for the region, and these suggestions are crucial for integrating them into new master plans. By adopting Sponge City principles, we can enhance the resilience of vulnerable areas and effectively manage water resources to reduce flood risk and protect both agricultural and built-up zones.
Hatay, Antakya example
Keywords: Sponge City; Floodplains; Agricultural areas; Built-up areas